Psychological Contract: Theoretical Dimensions, Literature Review and Research Agenda - Pinto, Prakash; Aranha, Rekha Hitha (Prabandhan: Indian Journal of Management, 2009)
The term 'Psychological contract' has been in the academic discussion since 1960s. As distinguished from a formal written contract of employment which only identifies mutual duties and responsibilities in a general form, a psychological contract represents the mutual beliefs, perceptions and informal obligations between an employer and an employee. It gives a practical approach to the contract of employment. Basically, the psychological contract gives the sum of beliefs held by an individual and his/her employer about their mutual expectations. A psychological contract creates emotions and attitudes in the employment relationship and hence to manage the employment relationship effectively it is necessary to understand the psychological contract with its various dimensions. The employment rights, duties and obligations emerge from the interpersonal relationships formed in the workplace and the way in which the managers, employees and supervisors behave on a day to day basis cannot be determined in a formal contract of employment. In fact, employees would negotiate to fulfil their side of desires and such negotiation more often takes the form of behavioural action and reaction. Therefore, a psychological contract determines what the parties to the contract of employment will or will not do and how they do it. However due to the unarticulated nature of the psychological contract, the fundamental problem is that the employees are not clear what they expect from their employers and some employers are not clear what they expect from their employees. It should be noted that the psychological contract governs the continuing development of the employment relationship but its impact may not be fully understood by the parties to the employment contract.